Pulses production in Italy: trade, marketing and policy issues - Ghelfi, Rino; Palmieri, Alessandro (Italian Journal of Agronomy, 2017)
Italian pulses production has sharply fallen since the middle of the last century and the role that pulses played has diminished at both the agricultural and food levels. This is the result of several factors that are analysed in this article, among which the most important can be identified in the low profitability compared to other crops, mainly cereals, the historic collapse of domestic consumption and a strong competition from foreign producers. Conversely, in recent years, different signals appear to delineate a possible framework for recovery for legumes: the first of these is represented by the recent reversal trend in domestic consumption, due to healthy reasons and a fall in meat consumption. The favourable trend of organic consumption can also be considered as a positive factor for pulses. However, the focus point for pulses future perspective is the recent development of the European policy (2014-2020) that planned several actions in support of them, such as coupled payments and the provisions of greening rules. These policies aim to support the training effort needed to bring home to producers the importance of legumes in a proper crop rotation that maintains soil fertility and therefore better yields and profitability. In light of this and based on the general crisis in cereals prices, it is possible to be reasonably optimistic regarding the future of the legumes sector in Italy.